If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) + 2x = 6 Reorder the terms: 5(-3 + x) + 2x = 6 (-3 * 5 + x * 5) + 2x = 6 (-15 + 5x) + 2x = 6 Combine like terms: 5x + 2x = 7x -15 + 7x = 6 Solving -15 + 7x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7x = 6 + 15 Combine like terms: -15 + 15 = 0 0 + 7x = 6 + 15 7x = 6 + 15 Combine like terms: 6 + 15 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 6w-8=-12 | | 6x-14x+3x=40 | | 8(-3x-2)=4(3x-1) | | 9x-2x-5x= | | -25=-150+q | | 2(m+2.5)=4(m-0.5) | | -3-7=8w+8v | | 35=d-12 | | 9=10r-16r+5r | | -18=-61+d | | -9v+2v=-7+14 | | -10+6m=2(5+5m) | | p=6s | | 2a-36-2c+5a-7c+8b= | | 10(x+4)=7(x-3) | | 15=t+8 | | 1-(m-1)=2(m-3) | | 19-7=2x+x | | 9y+3x=27 | | t-72=-44 | | e+5(e+1)=4(2e-2)+11e | | 5y-2y=12+14 | | 10x-7=2x+29 | | 32x=3x^2+90 | | -7(n+5)=-32-6n | | 1-1(m-1)=2(m-3) | | 4x+15+6=3x-14 | | 4b^2-12b+9=0 | | -(6c-5)=4(7c-8)+3 | | 18+z=34 | | 3-2x=5x+9-2x-15 | | 5(g-2)+g=6(g-4) |